The consequence of immersion time in chemical bath deposition on the properties of CuO thin films. (3rd October 2019) - Ramya, V.; Neyvasagam, K.; Chandramohan, R.; Mohan, R.; Valanarasu, S.; Franklin Benial, A. Milton
ABSTRACT: In this study, the effect of immersion time of the substrate in the chemical deposition bath on the physical properties of cupric oxide films is estimated by varying the immersion time as 15, 30, 45, 60 and 75 mins, respectively. The XRD studies revealed that the thin films showed a monoclinic structure with preferential orientation along (111) plane. Using X-ray profile analysis such as crystallite size, microstrain, dislocation density and stacking fault is estimated. Morphological studies revealed that the surface of films has uniformity and the particle size maximum for 45 min immersion time. In optical studies band gap, refractive index, extinction coefficient and optical conductivity have been estimated. The variations in immersion time had a considerable effect on the electrical parameters of films are confirmed. The studies revealed that the immersion time on CBD does have a significant role in deciding the property of the CuO thin films grown.